2007
DOI: 10.1097/mlg.0b013e318031d0b4
|View full text |Cite
|
Sign up to set email alerts
|

Demands on Caring Relatives of Head and Neck Cancer Patients

Abstract: This study shows the significant impact of cancer on caring relatives of head and neck cancer patients. In our opinion, health services should become more aware of this potential to ensure that the needs of the involved patient relatives are met as well as those of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 12 publications
4
45
1
Order By: Relevance
“…This realization has lead to a burgeoning literature assessing and comparing patient and partner distress levels 3,[31][32][33][34][35][36][37][38][39][40][41][42] as well as sex differences in distress. [43][44][45][46][47] With a few exceptions, 32 these studies suggest that patients report higher levels of clinically relevant distress than partners 3 and that women who are patients and partners report higher levels of distress than men who are patients and partners. 43 Recent reviews have suggested that the difference in distress levels between patients and partners can be accounted for by sex differences in the reporting of psychologic distress rather than role differences.…”
Section: Approaches To Understanding Cancer In the Marital Contextmentioning
confidence: 91%
See 1 more Smart Citation
“…This realization has lead to a burgeoning literature assessing and comparing patient and partner distress levels 3,[31][32][33][34][35][36][37][38][39][40][41][42] as well as sex differences in distress. [43][44][45][46][47] With a few exceptions, 32 these studies suggest that patients report higher levels of clinically relevant distress than partners 3 and that women who are patients and partners report higher levels of distress than men who are patients and partners. 43 Recent reviews have suggested that the difference in distress levels between patients and partners can be accounted for by sex differences in the reporting of psychologic distress rather than role differences.…”
Section: Approaches To Understanding Cancer In the Marital Contextmentioning
confidence: 91%
“…20 A second focus of this literature has been to study the psychologic impact of caregiving on spouses. The primary focus of these studies has been on quantifying caregiving demands 47 and identifying correlates of caregiver burden. 48 For a review of this literature, please see the article by Kim and Given in this supplemental issue of Cancer.…”
Section: Approaches To Understanding Cancer In the Marital Contextmentioning
confidence: 99%
“…8 The disease and its treatment can affect the patient's physical functioning and ability to communicate. 9 Head and neck cancer can impact on 1 or more of the physiological organs and tissue of the mouth, tongue, salivary glands, nasopharynx, oropharynx, laryngopharynx, larynx, nose, and paranasal sinuses. The impact of the cancer in conjunction with iatrogenic affects of surgery, radiotherapy, and chemotherapy (either as standalone treatments or more commonly in combination) causes detrimental effects on function.…”
mentioning
confidence: 99%
“…Those patients with severe symptoms and high care needs, like the relatives in our studies, experienced a difficult situation and required support and assistance, as reported in prior studies [171][172][173]. This casts light on how care requirements could possibly be reduced if the healthcare system expands care and support for patients and relatives.…”
Section: Relatives' Experiencessupporting
confidence: 51%